Identification of Novel GH-regulated Genes in C2C12 Cells - Resmini, E.; Morte, B.; Sorianello, E.; Gallardo, E.; de Luna, N.; Illa, I.; Zorzano, A.; Bernal, J.; Webb, S. M. (Hormone and Metabolic Research, 2011)
Growth hormone (GH) is the main regulator of longitudinal growth before puberty, and treatment with human recombinant (rh) GH can increase muscle strength. Nevertheless, molecular mechanisms responsible remain mostly unknown. Many physiological effects of GH require hormone-mediated changes in gene expression. In an attempt to gain insight into the mechanism of GH action in muscle cells we evaluated the effects of rhGH on gene expression profile in a murine skeletal muscle cell line C2C12. The objective of the work was to identify changes in gene expression in the murine skeletal muscle cell line C2C12 after rGH treatment using microarray assays. C2C12 murine skeletal muscle cell cultures were differentiated during 4 days. After 16 h growing in serum-free medium, C2C12 myotubes were stimulated during 6 h with 500 ng/ml rhGH. Four independent sets of experiments were performed to identify GH-regulated genes. Total RNA was isolated and subjected to analysis. To validate changes candidate genes were analyzed by real-time quantitative polymerase chain reaction. One hundred and fifty-four differentially expressed genes were identified; 90 upregulated and 64 downregulated. Many had not been previously identified as GH-responsive. Real-time PCR in biological replicates confirmed the effect of rGH on 15 genes: Cish, Serpina3g, Socs2, Bmp4, Tnfrsf11b, Rgs2, Tgfbr3, Ugdh, Npy1r, Gbp6, Tgfbi, Tgtp, Btc, Clec3b, and Bcl6. This study shows modifications in the gene expression profile of the C2C12 cell line after rhGH exposure. In vitro and gene function analysis revealed genes involved in skeletal and muscle system as well as cardiovascular system development and function.
Keywords: skeletal muscle; microarrays; growth hormone; cell cultures